The basics of applying a pause in imprisonment - Mrozek, Kamila (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
A pause in punishment is one of most effective alternatives to the absolute punishment of imprisonment. It can be applied only if the convicted has already started serving the sentence of imprisonment. The execution penal code takes into consideration a two — basis pause in punishment: obligatory, connected with health and optional, related to family and the personal situation of the convicted. The competent court is the penitentiary, in whose district the convicted resides. The pause in punishment is an exception to the fundamental rule of uninterrupted execution of the sentence, so due to its unique character it should be granted with regard to anarrow understanding of statutory requirement.
Keywords: kara pozbawienia wolności; przerwa w wykonywaniu kary; choroba psychiczna; sąd penitencjarny; ważne powody rodzinne; ważne powody osobiste